Divertor Tokamak Test: Impact of NBI shine-through and beam-plasma interaction on Divertor Tokamak Test facility - De Piccoli, C.; Vincenzi, P.; Veronese, F.; Agostinetti, P.; Casiraghi, I.; Castaldo, A.; Mantica, P.; Murari, A.; Bolzonella, T. (Frontiers in Physics, 2024)
IntroductionIn this work, we aim to explore numerically the behavior of beam energetic particles in the Divertor Tokamak Test (DTT), a superconductive device equipped with a Neutral Beam Injection (NBI) system capable of injecting neutrals up to 510 keV.MethodWe explore beam ionization and beam slowing down for different DTT plasma scenarios. Numerical simulations are performed using the ASCOT suite of codes, including a wide-range scan of plasma density and beam injection energy. For different plasma conditions, we estimate shine-through losses, including the heat fluxes on the first wall thanks to dedicated particle tracing simulations. Orbits of newly-born fast ions are characterized by means of the constant of motion phase space, showing how trapped energetic particles’ population and prompt losses change with plasma density and NBI energy.Results and discussionSlowing down simulations show that NBI injection at 510 keV is well coupled to DTT plasmas. DTT NBI will be one of the sources of auxiliary ion heating, with an absorbed power ratio of up to ∼50% depending on plasma and beam parameters. At low plasma densities, energetic particle confinement is less efficient, and NBI power and/or energy reduction is expected.